PROSES PENYUSUNAN RENCANA BISNIS DAN ANGGARAN PADA BADAN LAYANAN UMUM RSUD SUMBERGLAGAH - Sugiarto, Adi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is: (1) to find out and to understand the general description in the preparation of the business planning and budgeting by using financial management pattern of public service area. (2) to find out and to understand the process of business planning preparation and budgeting at Public Service Agency of Regional General Hospital Sumberglagah. The data collection technique in this research is carried out by using literature and field research, while the data analysis technique in this research is carried out by using descriptive with qualitative approach by collecting data which is related with the process of business planning preparation and Budgeting at Regional General Hospital Sumberglagah. The analysis result on the process of business planning and budgeting at Regional General Hospital Sumberglagah in general has already run well because it has been implemented all the components and flow in accordance with the procedure, however it shows some weaknesses or flaw in the components in the process of business planning preparation and budgeting that has been done conducting, it doesnât fulfill the substance in the preparation component when preparing the business planning and budgeting, which are analysis recorded and per â unit cost estimation is not good. Since there is substance in the analysis recorded and cost estimation is still using cash basis on component and substation in the process of business planning and budgeting has caused inaccuracy. It is suggested that an institution should do the improvement in the process of business plan and budgeting that is in the financial report in the recognition of the income and expenditure in the budgeting realization in the substance analysis recording and per â unit cost estimation in the component of business plans and budgeting, by using accrual base. By using different accounting base as the foundation on financial reports which is used as the preparation materials in the component of business planning and budgeting, so the preparation contents of business planning and budgeting in the income recognition and expenditure in the budgeting realization in the substance of analysis recording and the estimation of per â unit cost in accordance with The Government Regulation number 71 in the year of 2010 about the Government Accounting Standard should apply the accrual base completely. Keywords: Public Service Budget Agency, Budgeting Allocation, Business Planning and Budgeting.